2019
DOI: 10.3390/genes10040256
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Global DNA Methylation Changes Associated with Plasticity in Seven Highly Inbred Lines of Snapdragon Plants (Antirrhinum majus)

Abstract: Genetic and epigenetic variations are commonly known to underlie phenotypic plastic responses to environmental cues. However, the role of epigenetic variation in plastic responses harboring ecological significance in nature remains to be assessed. The shade avoidance response (SAR) of plants is one of the most prevalent examples of phenotypic plasticity. It is a phenotypic syndrome including stem elongation and multiple other traits. Its ecological significance is widely acknowledged, and it can be adaptive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 88 publications
(122 reference statements)
2
16
0
Order By: Relevance
“…Epigenetic characterization of variants at the scale of populations, which is necessary for epibreeding, is also limiting. These population level approaches lack precision (Gourcilleau et al., ). Technological progress is fast, and these problems will soon be solved.…”
Section: On the Nature Of Epibreedingmentioning
confidence: 99%
“…Epigenetic characterization of variants at the scale of populations, which is necessary for epibreeding, is also limiting. These population level approaches lack precision (Gourcilleau et al., ). Technological progress is fast, and these problems will soon be solved.…”
Section: On the Nature Of Epibreedingmentioning
confidence: 99%
“…This addition is provided de novo and maintained by methyltransferase enzymes through three different sequence contexts in plants: CG, CHG and CHH (Meyer 2015). Over recent years, many studies have highlighted the role of DNA methylation in many biological and ecological mechanisms in plants, such as development (Guo et al 2018, responses to biotic and abiotic stressors (Tricker 2015, Crisp et al 2016, Lämke and Bäurle 2017, cellular-stress response memory and priming (Mauch-Mani et al 2017, Sow et al 2018, phenotypic plasticity (Gourcilleau et al 2010, Baulcombe and Dean 2014, Kooke et al 2015, Conde et al 2017, and possibly adaptation (Bräutigam et al 2013, Kawakatsu et al 2016, Rey et al 2016, Schmid et al 2018, Gourcilleau et al 2019. Kooke et al (2015) used 99 Epigenetic Recombinant Inbred Lines (epiRILs) of Arabidopsis thaliana, consisting of crosses between the parents Col-0 and the hypomethylated mutant lines ddm1 and ddm2, to compare the morphological responses of the plants exposed to saline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5]. It is also shown that epigenetic modifications can be associated with the magnitude of change in reaction norms of some but not all phenotypic traits [6]. In addition, even when considering the same bearer of epigenetic information (e.g., DNA methylation), different organisms show different types of DNA methylation (e.g., [1][2][3][4][5][6]) with potentially different types of phenotypic effects.…”
mentioning
confidence: 99%
“…It is also shown that epigenetic modifications can be associated with the magnitude of change in reaction norms of some but not all phenotypic traits [6]. In addition, even when considering the same bearer of epigenetic information (e.g., DNA methylation), different organisms show different types of DNA methylation (e.g., [1][2][3][4][5][6]) with potentially different types of phenotypic effects. Nevertheless, epigenetic changes do not occur randomly along the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation